Risk assessment of human-to-human transmission of severe fever with thrombocytopenia syndrome virus based on 10-year clustered analysis - Zhang, Nannan; Mu, Xiaodong; Liu, Jingyu; Liu, Tao (Frontiers in Public Health, 2024)
Severe fever with thrombocytopenia syndrome (SFTS) is an acute infectious disease firstly reported in 2009 in China. Rarely study have quantitatively assessed the transmission and fatal risk among SFTS clusters.Epidemiological information regarding SFTS clusters in Yantai of Shandong province during 2013-2022 were obtained from the National Public Health Emergency Event Surveillance System for Disease Control and Prevention Information System.Secondary attack rate (SAR) and relative risk (RR) were used to access the risk of SFTS human-to-human transmission.There were 20 SFTS clusters involving 51 laboratory confirmed patients were reported between 2013 and 2022 in Yantai city, Shandong province. Most clusters were occurred from May to October and patients mainly distributed in 4 counties.Blood or other fluids contact [RR=14.06, 95%confidence interval (CI)= 3.29-70.65, P < 0.001] and using no personal protection equipment (PPE) [11.63% (10/86) vs 2.22% (2/90), RR = 5.74, 95% CI=1.17-55.44, P =0.013] were significantly related with increased risk of STFSV transmission.Our study may provide direct guidance on health education and behavioral interventions for relatives and accompanying personnel of the SFTS cases in hospital and returning home after discharge.